’Phōtós’: Essay on Light and Image - Torres Sánchez, Rayiv David (Escritura e Imagen, 2019)
How to remember an image? What is the nature of that survivor rest which makes it possible to contact between images and their “original sources”? Assists us how the emergence of which already cannot be seen? Throughout this exhibition it is interrogará about the way in which systems of thought have been on basis optical, heliocentric, claiming “illuminated the truth” under the guarantee of the light and “tailored to the eye”. But we will see that this would also be the risk of an incandescence that throughout the history of Western thought implies that you make that lack definition and booking, this isolation and this strangeness that preserves for himself everything that can be put ca balmente exposed to preserve a lustral incineration. This would be the case of an “original expression” of the imagination through the images, to talk not only of a neutral and founding void, but also mix different sources of similarity and dissimilarity, the appearance and beauty, dreams and fascination.